An evaluation of treatment recommendations: a comparative analysis between tlicss and tlaosis in thoracolumbar spine injuries - Niaz, Murk; Muhammad Faaiq Ali; Amina Shamshad Khokhar; Muhammad Sameer Khulsai; Farhad Ali; Inayat Ali Khan (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the treatment recommendations of the thoracolumbar injury classification and severity score system and the thoracolumbar Arbeitsgemeinschaft für Osteosynthesefragen spine injury score in case of thoracolumbar spine injury. Method: The cross-sectional study was conducted at the Shaheed Mohtarma Benazir Bhutto Institute of Trauma, Karachi, from July to December 2023, and comprised patients aged at least 18 irrespective of gender, who had traumatic thoracic and lumbar vertebral spine fractures. Data regarding age, gender, mode of trauma, findings of neurological examination and imaging was collected. All cases were independently scored by an experienced spine surgeon, and a radiologist provided standardised imaging interpretation. The scorers were blinded to clinical outcomes and treatment decisions. Inter-rater agreement between thoracolumbar injury classification and severity score system and the thoracolumbar Arbeitsgemeinschaft für Osteosynthesefragen spine injury score was assessed using Cohen's kappa coefficient. Data was analysed using SPSS 23. Results: Of the 335 patients with mean age 32.24±13.32 years, 279(83.3%) were males. The most common mode of trauma was fall from height 189(56.4%), and the most common site of fracture was L1 vertebrae 109(32.5%). Based on the thoracolumbar injury classification and severity score system, the most common fracture morphology was burst fracture 257(76.7%). The most common fracture type based on the thoracolumbar Arbeitsgemeinschaft für Osteosynthesefragen spine injury score was Type A compression injuries 300(89.6%). The thoracolumbar Arbeitsgemeinschaft für Osteosynthesefragen spine injury score had more patients in the grey zone 30(9%) compared to thoracolumbar injury classification and severity score system 22(6.6%). Treatment recommendations were the same in both the classification systems for 306(91.3%) patients (Cohen's kappa = 0.812, p<0.001). Conclusion: There was no significant difference between the treatment recommendations suggested by the thoracolumbar injury classification and severity score system and the thoracolumbar Arbeitsgemeinschaft für Osteosynthesefragen spine injury score. The differences in grey zone classification highlighted the complexity of thoracolumbar injury assessment. Key Words: TLICSS, TLAOSIS, Thoracolumbar spine, Fracture.